ANALISIS TEKNIK PASSING BAWAH DALAM PERMAINAN BOLA VOLI PADA EKSTRAKURIKULER MTSN 6 BATANGHARI - Afriansyah, A.Padli; Palmizal A.; Saputra, Adhe (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to analyze underhand passing techniques in volleyball at the MTSN 6 Batanghari volleyball extracurricular activity.This research is a survey study using a quantitative descriptive method. Data collection techniques include tests and measurements, providing a numerical overview of the research topic. The sample used in this study was a total sampling technique, consisting of all 15 students participating in the volleyball extracurricular activity at MTSN 6 Batanghari.The results of the study show that the results obtained from the underhand passing technique test in volleyball games that have been carried out, the average percentage results obtained in the very good category are 1 person with a percentage of 7%, in the good category there are 9 people with a percentage of 60%, in the moderate category there are 5 people with a percentage of 33%.The conclusion of this study is that the underhand passing technique in volleyball games that have been carried out, the average percentage results obtained in the very good category are 1 person with a percentage of 7%, in the good category there are 9 people with a percentage of 60%, in the moderate category there are 5 people with a percentage of 33%.